Criação de um Framework para desenvolvimento de aplicações descentralizadas baseadas em redes Blockchain - Frank Castilio Pinheiro de Alencar (2024)
Based on Blockchain networks, decentralized applications (DApps) are expanding. Research shows that these applications have been created without following methodological criteria for software development. Therefore, it is important to systematize their construction so that developers can focus on their research problem. The lack of clear guidelines for creating DApps is a challenge and hinders the entry of new researchers and developers into this field. Research attempting to fill this gap often addresses specific issues in the DApp development process. Thus, this work relied on a systematic literature review (RSL) and created a framework to assist in DApp development, specifically in decision-making about which decentralized platform to use to host the application, conceptualizing and discussing the technologies used in each stage of this process. The RSL revealed the absence of a similar structure to the one developed in this work, the framework provides guidance for selecting the decentralized platform according to the DApp's requirements.